Big daddy - Stewart, Jon, 1962-; Sandler, Adam.; Dugan, Dennis; Schneider, Rob, 1963-; Adams, Joey Lauren (Culver City, Calif. : Columbia TriStar Home Video, 1999)
Thirty-two-year-old Sonny Koufax has spent his whole life avoiding responsibility. But when his girlfriend dumps him for an older man, he's got to find a way to prove he's ready to grow up. In a desperate last-ditch effort, Sonny adopts five-year-old Julian to impress her. She's not impressed...and he can't return the kid.
Widescreen and full screen versions.
Home use only.
Screenplay by Steve Franks and Tim Herlihy and Adam Sandler ; directed by Dennis Dugan.
Adam Sandler with Joey Lauren Adams, Jon Stewart, Rob Schneider, Cole Sprouse, Dylan Sprouse and Leslie Mann.
Video rating : PG-13.
DVD.
Keywords: Bachelors -- Drama; Adoptive parents -- Drama; Feature films; Comedy films; Films for the hearing impaired